Diversity of macrofaunal Mollusca of the abyssal Vema Fracture Zone and hadal Puerto Rico Trench, Tropical North Atlantic. (February 2018) - Linse, Katrin; Schwabe, Enrico
Abstract: While biodiversity patterns of Atlantic deep-sea bivalves and gastropods have served as model taxa for setting global latitudinal and bathymetric hypotheses, less is known on abyssal, amphi-Atlantic molluscan assemblage compositions. The Vema-TRANSIT expedition sampled 17 stations in the Vema Fracture Zone (VFZ) and the Puerto Rico Trench (PRT) by epibenthic sledge. These samples comprised a total of 1333 specimens and 64 morphospecies of the classes Caudofoveata (7 species), Solenogastres (7 spp.), Bivalvia (22 spp.), Gastropoda (24 spp.), and Scaphopoda (4 spp.) while Cephalopoda, Monoplacophora and Polyplacophora were absent. The majority of species was rare with 21 uniques (32.8% of all species) and 10 duplicates (15.6% of all species) and of these 15 (48% of rare/23.4% of all species) morphospecies were singletons and 8 (25.8% of rare/12.5% of all species) morphospecies were doubletons. Overall bivalves (686 specimens) were most abundant, followed by scaphopods (314 spec.), while solenogastres (180 spec.), caudofoveates (86 spec.) and gastropods (67 spec.) were less abundant. The abyssal macro-molluscan species composition did not vary significantly between the eastern and western Atlantic sides of the VFZ while abundances standardized to 1000 m 2 trawled area were higher on the eastern side. The abyssal PRT stations resembled the VFZ ones in species composition and abundances, in the latter the eastern VFZ. The hadal PRT differed in species composition from the abyssal VFZ and PRT and abundances were similarly low like the western VFZ. The Mid-Atlantic Ridge appeared not to be a barrier for the dispersal of the mostly lecitotrophic or plankotrophic larval stages of the reported molluscan species in this study.